Ron Kerle and Norman Boughen interviewed by Mark Schuster and Maria Zann in the Mark Schuster and Maria Zann folklore collection. - Kerle, Ron.; Boughen, Norman; Schuster, Mark.; Zann, Maria (1997)
Folkloric recording.
Ron Kerle and Norm Boughen (accompanying) play a number of regional German-Queensland dance tunes and old-time popular tunes on button accordian and discuss German-Queensland history and culture of the Minden and eastern Lockyer area.
Catalogue record generated as part of a batch load.
Recorded on 19 March 1997 in Minden, Queensland.
Digital master available
Summary not yet available.
Keywords: Boughen, Norman -- Interviews; Kerle, Ron -- Interviews